Towards Affordable Low Cost Housing: Strategies of Low Cost Housing Development for the Low Income Population in Rwanda (Global Journal of Management and Business Research, 2018)
Abstract not found
Keywords: affordable housing; finance; strategies; challenges; low cost housing